Investigating the Effects of Performing the Early Mobilization Protocol on Postoperative Hemorrhaging in Cardiac Surgery Patients - Hanie Dahmardeh (Archives of Anesthesia and Critical Care)
Background: Most adverse effects following cardiac surgery, including hemorrhaging, are related to immobility. The early mobilization of the patient in enhanced recovery after surgery (ERAS) can counteract these adverse effects. Despite the awareness, however, the protocol has a low performance rate due to numerous barriers. The present research aims to investigate the effectiveness of performing the early mobilization protocol on hemorrhaging in cardiac surgery patients. Methods: This research is a clinical trial study conducted in 2023-2024 at Ali Ibn AbiTalib Hospital in Zahedan, Iran, on 100 patients undergoing cardiac surgery. Purposive sampling was used based on the inclusion criteria. Hemorrhaging risk assessment in patients was evaluated according to the preoperative checklist. The early mobilization protocol was performed on day 2 after surgery on patients in the intervention group with mild to low risk of hemorrhage. The statistical tests of repeated measures, chi-square, and independent t-test were used for data analysis in SPSS 26. Results: There were no statistically significant variations in the demographic characteristics of patients in the intervention and control groups. The mean and standard deviation (SD) of the blood volume loss in patients over three different time periods (days 2, 3, and 4 after surgery) were 326.500±16.81, 69.300±11.41, and 51.200±3.82 in the intervention group, respectively, and 350.00±16.81, 325.00±11.41, and 82.10±3.82 in the control group, respectively, indicating the effectiveness of performing the early mobilization protocol (P ˂ 0.001). Conclusion: Performing the early mobilization protocol can reduce the volume of bleeding after cardiac surgery and the early discharge of patients, thus leading to reduced complications. Nurses as the main care providers in intensive care units play a key role in performing the protocol.